Copy Number Variations with Isolated Fetal Ventriculomegaly - Hu, P.; Wang, Y.; Sun, R.; Cao, L.; Chen, X.; Liu, C.; Luo, C.; Ma, D.; Wang, W.; Fu, X.; Shi, W.; Yi, S.; et al. (Current Molecular Medicine, 2017)
Background: Copy Number Variations (CNVs) are an important genetic cause of a number of neurodevelopmental disorders (NDs). However, the association between CNVs and the development and prognosis of fetal isolated mild ventriculomegaly (IMV) is unclear. Objectives: To investigate possible associations between CNVs and the development of fetal IMV. Methods: This retrospective study recruited 154 subjects with ultrasound-confirmed fetal IMV and 190 subjects in a control cohort who underwent a high-risk prenatal serum screening program. The exclusion criteria included fetus G-banding chromosomal abnormality or positive fetus TORCH infection. DNA samples from all 344 fetuses were examined by an SNP-array. Developmental outcomes were assessed during postnatal follow-up. Results: Fourteen pathogenic CNVs (pCNVs) were identified in 13 out of 154 IMV fetuses. Three pCNVs were found in 3 out of 190 subjects in the prenatal screening high-risk cohort, with a significant difference (P value=0.016, X2 test). Notably, the 14 pCNVs detected in the IMV cohort were all associated with neurodevelopmental disorders (NDs), including autism, intellectual disability. Among the 13 IMV fetuses carrying pCNVs, five subjects were found in the postnatal follow-up to manifest NDs, including two with autism and three with mild neurodevelopmental delay. The other 8 subjects consisted of three normal infants younger than 12-months old, two lost in the follow-up, and three with the termination of pregnancy. Out of 141 IMV subjects without detectable pCNVs, 123 subjects showed normal development, 16 were lost in the follow-up, 2 subjects terminated the pregnancy due to fetal hydrocephalus or congenital heart disease in the late fetus development. Conclusions: This study suggests an association between pCNVs and fetal IMV. pCNVs may be involved in the pathological process of fetal IMV and postnatal NDs. Identifying specific genomic alterations may provide an insight into pathogenetic mechanism and aid better diagnosis and prognosis of neurodevelopmental outcomes in fetal IMV.
Keywords: prenatal diagnosis